Ethical aspects of nursing research - Alexsandra Rodrigues Feijão (Universidade Federal do Ceará, 2014)
With the advances of nursing scientific production in recent decades, in tandem with the growth of nursing postgraduate programs in Brazil, the discussion about ethics in research with human beings is perennial and relevant to nursing research.